A Dictionary of Economics - Hashimzade, Nigar (Oxford Quick Reference Ser, 2017)
This bestselling and authoritative dictionary covers all aspects of economics including theory, policy, and applied micro and macroeconomics on a global scale. An essential book for professional economists as well as for students and teachers of economics, business, and finance